Analisis Presepsi Penggunaan Aplikasi BRImo Dengan Pendekatan Technology Acceptance Model (TAM) Mahasiswa Universitas Merdeka Malang - Azhari, Ivan Dwi Nur (Universitas Muhammadiyah Surabaya, 2025)
Bank Rakyat Indonesia (BRI) is one of the largest government-owned banks in Indonesia. In the development Â of digital era like this, online services become the choice of most of the clients. This is due to ease of doing any kind of banking transaction. Along with the inclusion of smartphones as a device that is needed by most people today, the Bank BRI provides Mobile Banking facilities named